2020
DOI: 10.1007/s00296-020-04644-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perioperative interventions targeting psychological distress on clinical outcome after total knee arthroplasty

Abstract: Our aim was to assess the effect of perioperative interventions targeting psychological distress on clinical outcome after total knee arthroplasty (TKA). We searched studies on the effect of perioperative interventions focused on psychological distress used in conjunction with TKA on pain, function, and quality of life (QoL) on PubMed, Embase.com, PsycINFO/OVID, CENTRAL, the Cochrane Database of Systematic Reviews, Scopus, and Web of Science. We included 40 studies (22 RCTs, ten cohort studies, and eight quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 72 publications
(168 reference statements)
0
15
0
Order By: Relevance
“…Other studies are less distinct and did not find a relationship between anxiety and suboptimal outcomes (Wood et al 2021). Nevertheless, previous studies showed that psychological support might lead to lower incidence of pain, anxiety/depression, and improve faster recovery (Tristaino et al 2016, Sorel et al 2020. Preoperative analysis of the presence of these factors and concomitant treatment might be an effective way to improve the satisfaction rate of TKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies are less distinct and did not find a relationship between anxiety and suboptimal outcomes (Wood et al 2021). Nevertheless, previous studies showed that psychological support might lead to lower incidence of pain, anxiety/depression, and improve faster recovery (Tristaino et al 2016, Sorel et al 2020. Preoperative analysis of the presence of these factors and concomitant treatment might be an effective way to improve the satisfaction rate of TKA.…”
Section: Discussionmentioning
confidence: 99%
“…This might be feasible with the Pain Catastrophizing Scale (PCS) or Hospital Anxiety and Depression Scale (HADS) (Mercurio et al 2020). The recently published systematic review by Sorel et al is promising and described various interventions with good effect on postoperative pain, quality of life, and function for psychological distress in TKA patients (Sorel et al 2020). Therefore further studies are needed to identify these patients preoperatively and to examine in which way adequate therapy can be provided in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Several modifiable risk factors have been reported that could reduce pain before surgery: losing weight, healthier dietary choices, levels of physical activity, use of assistive devices (i.e. insoles), decrease the number of medical comorbidities, pain catastrophizing and coping, and psychological factors, such as anxiety, distress and depression might also affect postoperative pain [ 5 , 32 , 41 , 42 ]. Sorel et al [ 42 ] showed that perioperative interventions targeting psychological distress resulted in improved pain scores or decreased opioid or other types of pain medication prescriptions after TKA.…”
Section: Discussionmentioning
confidence: 99%
“… 92 Although not all of the evidence included in the meta-analysis was for psychotherapy, the results suggest that interventions targeting psychological distress in patients with TKA are very attractive directions for treatment. 92 …”
Section: Management Of Depression In Oamentioning
confidence: 96%
“… 91 A more recent meta-analysis included 40 studies. 92 It concluded that perioperative interventions targeting psychological distress had a positive effect on postoperative pain, function, and QoL for patients who underwent TKA. 92 Although not all of the evidence included in the meta-analysis was for psychotherapy, the results suggest that interventions targeting psychological distress in patients with TKA are very attractive directions for treatment.…”
Section: Management Of Depression In Oamentioning
confidence: 99%